A espiritualidade como estratégia de enfrentamento do paciente oncológico no percurso da enfermidade - Silva, Renata Rose Pachêco da (2009)
The fundamental goal of this paper is to find resources of spiritual matter that, especially, strengthen and encourage women with either breast or colon cancer, transforming them into a coping strategy. This qualitative research approach, with a communicative nature was composed by a group of seven participants of the female gender. All of them were in the remissive phase of the treatment and belonged to the Grupo de Apoio Esperança (supporting group hope), which offers psychological support to CEOC (Centro de Oncologia de Caruaru - PE- Caruaru´s Cancer Treatment Center) patients who suffer from cancer. The data was collected by the interview technique, in 2008 November. Was used for analysys the method of data condensation based on the Kvale (1996) applications. It was observed that for patients that carry either breast or colon cancer the most commonly used coping strategy is the search for spirituality